Possibilities of the combined use of non-steroidal anti-inflammatory drugs and sulfhydryl compounds in radioprotection - Kozubík, A; Pospísil, M; Netíková, J (Strahlentherapie und Onkologie, 1991)
The combined preirradiation administration of indomethacin and cystamine was found to enhance synergistically the recovery of hemopoiesis in sublethally gamma-irradiated mice. This effect can be explained by a common operation of two mechanisms of radioprotection, i.e. of an increased survival of hemopoietic stem cells due to cystamine action and of stimulatory effects of indomethacin on the proliferation of surviving cells, mediated by the inhibition of prostaglandin synthesis. Attempts to prove such enhancement of protective effects on irradiated mice in terms of postirradiation lethality were unsuccessful. The reason seems to be the influence of toxic effects of the indomethacin-cystamine combination on the gastrointestinal tract. When using the less toxic combination, i.e. diclofenac and WR-2721, the additivity of protective effects is manifested even in the survival of lethally irradiated mice. The results suggest that under suitable conditions avoiding the unfavourable toxic effects, non-steroidal anti-inflammatory drugs can be successfully used with the aim to enhance the efficiency of sulfhydryl radioprotectors.
Keywords: dávka záření; Mice, Inbred CBA; Hematopoiesis; sulfhydrylové sloučeniny; Drug Combinations; Male; hodnocení léčiv; Diclofenac; Indomethacin; mužské pohlaví; Amifostine; Drug Synergism; Radiation Dosage; synergismus léků; Anti-Inflammatory Agents, Non-Steroidal; antiflogistika nesteroidní; Time Factors; Animals; Cystamine; Sulfhydryl Compounds; zvířata; hematopoéza; amifostin; myši inbrední C57BL; časové faktory; myši; diklofenak; cystamin; Mice, Inbred C57BL; Drug Evaluation; celotělové ozáření; indomethacin; Mice; Radiation-Protective Agents; Whole-Body Irradiation; fixní kombinace léků; radioprotektivní látky; myši inbrední CBA